Avaliação biofísica para o gerenciamento ambiental da área de preservação permanente da bacia hidrográfica do Puraquequara - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The Amazon rainforest is home to the greatest diversity of plants and animals among all biomes on Earth. Ecosystems is of greater richness and diversity on the planet and performs environmental services of great relevance. However, changes in these ecosystems have been intensively occurring with increasing human occupation. With the creation of permanent preservation areas, the objective is to promote the protection of the natural environment of these areas that must be covered by native vegetation, contributing in this way, as a central pillar in the role of local biodiversity conservation. In this sense, this research aimed to answer the following problem: "The designation of the basin as Puraquequara Environmental Preservation Area in the Master Plan of the city of Manaus, in fact ensured the preservation of that area?". Are described biophysical impacts identified in the area as well as the possible causative agents. The results allow us to affirm that the performance of polluting activities generated large negative environmental impact on the area, leaving the competent authorities require the entrepreneur to taking immediate actions for the recovery of the affected environment, requiring the recipient to actually take the recommended action and making feasible administrative measures and appropriate legal action against those responsible.
Keywords: Área de preservação permanente; Impactos biofísicos; Análise ambiental; Permanent preservation area; Biophysical impacts; Environmental analysis; Proteção ambiental; CIÊNCIAS AGRÁRIAS: AGRONOMIA: RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL